A Review on Homoeopathic Remedies and their Relationship - Bala, Renu; Srivastava, Amit (Homœopathic Links, 2019)
The word relationship indicates the way in which two or more things are connected, or the state of being connected. There is nothing in nature really unrelated to anything else. Medicines are interrelated to each other in various ways of therapeutic action. Knowledge of these relations is very important for accurate prescribing. Hahnemann was always careful to observe and record the antidotes to the remedies he proved.The relationship of remedies is the most useful section in therapeutic pocket book. Even Kent advocated the use of this particular section which can be studied at various levels of mind, parts, sensations, modalities, etc. But it is the least understood and least used because of neglect on the part of physicians. The practitioners are mastering the art of individualisation which is one of the pillars of homoeopathic treatment but more stress needs to be laid upon the grouping of remedies based on their relationship which has great importance in practice for the ideal cure. The homoeopathic literature was found to be very rich in describing the relationship which every remedy owes to each other. This review aims to bring forward the underlying facts and experiences of different authors regarding remedy relationship.
Keywords: relationship; homoeopathic remedies; antidote; complementary